APPLICATION OF RETORTED OIL SHALE AS A SOIL AMENDMENT IN AN ARENIC SOIL: STRUCTURAL AND CHEMICAL CHANGES IN HUMIC ACIDS AFTER SIX YEARS: APLICAÇÃO DE XISTO BETUMINOSO RETORTADO COMO CORRETIVO DE SOLO EM UM SOLO ARENOSO: ALTERAÇÕES ESTRUTURAIS E QUÍMICAS NOS ÁCIDOS HÚMICOS APÓS SEIS ANOS - Gonçalves , Mayara Gabriela; Batista, Estela Mari Da Cunha Cardoso; Martinazzo , Rosane; Fornari, Mayara Regina; Silveira , Carlos Augusto Posser; Bamberg, Adilson Luís; o Dias Júnior , Lauro Camargo; Messerschmidt , Iara (Revista Brasileira de Meio Ambiente & Sustentabilidade, 2026)
Retorted oil shale (ROS) is the main byproduct of oil shale mining, and its application to soils has been considered a sustainable strategy for supplying low-cost fertilizers. Previous studies have shown that, after six years of cumulative ROS application, no significant increases in soil nutrient content or water retention capacity were observed, without compromising food and environmental safety. However, soil organic matter (SOM) dynamics are often early indicators of soil quality improvement, and the chemical and structural transformations of SOM after ROS application remain poorly explored.In this study, a field experiment investigated the effects of cumulative ROS application on humic acids (HA) isolated from an Arenic Rhodic Acrisol after six years. The HAs were characterized by diffuse Fourier transform infrared spectroscopy, fluorescence spectroscopy, electron paramagnetic resonance, thermogravimetric analysis, and elemental analysis.Multivariate analysis revealed that humic acids from soils receiving combined ROS and NPK application differed clearly from control treatments, showing increased aromaticity, higher C/N ratios, and a greater degree of humification, indicating a synergistic effect.These results suggest that, although the experimental period was insufficient to achieve advanced soil quality improvement, it promoted initial qualitative transformations in SOM that precede detectable changes in soil chemical and physical properties.